2021
DOI: 10.3390/rs13152906
|View full text |Cite
|
Sign up to set email alerts
|

Sinkhole Scanner: A New Method to Detect Sinkhole-Related Spatio-Temporal Patterns in InSAR Deformation Time Series

Abstract: Sinkholes are sudden disasters that are usually small in size and occur at unexpected locations. They may cause serious damage to life and property. Sinkhole-prone areas can be monitored using Interferometric Synthetic Aperture Radar (InSAR) time series. Defining a pattern using InSAR-derived spatio-temporal deformations, this study presents a sinkhole pattern detector, called the Sinkhole Scanner. The Sinkhole Scanner includes a spatio-temporal mathematical model such as a 2-dimensional time evolving Gaussian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The estimated deformation velocity showed clusters of significantly high subsidence velocities, ∼ −20 to −25 mm•yr −1 over the mining area near the sinkhole site. This is also similar to what was observed in [18]. Over the study area, the CCS spatial density was found to be low because of nature of the study area which is predominantly rural.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The estimated deformation velocity showed clusters of significantly high subsidence velocities, ∼ −20 to −25 mm•yr −1 over the mining area near the sinkhole site. This is also similar to what was observed in [18]. Over the study area, the CCS spatial density was found to be low because of nature of the study area which is predominantly rural.…”
Section: Discussionsupporting
confidence: 87%
“…Some of the applications of TSInSAR include monitoring of urban infrastructure [10]- [12], dam infrastructure [13], [14], geohazards such as volcanoes [15], [16] and sinkholes [17], [18]. TSInSAR is by now well established method to study spatio-temporal ground deformation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated deformation velocity showed clusters of significantly high subsidence velocities, ∼ −20 to −25 mm•yr −1 over the mining area near the sinkhole site. This is also similar to what was observed in [78]. Over the study area, the CCS spatial density was found to be low because of nature of the study area which is predominantly rural.…”
Section: Discussionsupporting
confidence: 87%
“…Persistent Scatterers [15], or Distributed Scatterers [14,18]. Some of the applications of TSInSAR include monitoring of urban infrastructure [72,73,74], dam infrastructure [75,76], geohazards such as volcanoes [48,77] and sinkholes [7,78]. TSInSAR is by now well established method to study spatio-temporal ground deformation patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation